Climate Change Vulnerability of American Lobster Fishing Communities in Atlantic Canada - Greenan, Blair J. W.; Shackell, Nancy L.; Ferguson, Kiyomi; Greyson, Philip; Cogswell, Andrew; Brickman, David; Wang, Zeliang; Cook, Adam; Brennan, Catherine E.; Saba, Vincent S. (Frontiers in Marine Science, 2019)
Climate change impacts on fisheries will undoubtedly have socio-economic impacts on coastal communities and the seafood market. However, it is a challenge to integrate climate change information in a form that can be used efficiently by adaptation planners, policy makers and fishery managers. In this study, we frame a climate change impact assessment using a geographical perspective based on the management units of the dominant fishery, in this case, American lobster in Nova Scotia, Canada. The information considered here includes economic dependence on the fishery, population size, diversity of the fishery revenue, status of harbour infrastructure, total replacement cost of each harbour, increased relative sea level and flooding, and the vulnerability of offshore lobster to ocean warming and changes in zooplankton composition and anticipatory changes in fishery productivity across management borders. Using two ocean models to provide multi-decadal scale projections of bottom temperature, changes in offshore lobster distribution are projected to have a neutral, or positive impact on the region as a whole. However, when lobster vulnerability is combined with climate change related vulnerabilities of coastal fishing communities, it is evident that adaptation planning is needed for long-term sustainability. This impact assessment provides both a framework and information for further in-depth analyses by climate change adaptation planners and fishery managers.